Board of Commissioners’ Relationship and Climate Change Disclosure: Evidence from Mining Companies - Ariani, Kurnia Rina; Rita Wijayanti; Mujiyati; Farid Adi Prasetyo; Maria Cristina M. De los Santos (Riset Akuntansi dan Keuangan Indonesia, 2023)
Climate change is one of the most important environmental challenges, with academics, corporate practitioners, and governments all paying close attention. The purpose of this study is to investigate the impact of board qualities such as independence, nationality, and busyness on climate change disclosure. The study consists of 44 samples and 216 data observations. Secondary data were gathered from annual reports issued by sample companies between 2018 and 2022. Darus et al. (2020) generated 19 carbon emission disclosure items, which were subjected to content analysis. According to the conclusions of the study, a bigger proportion of independent commissioners and commissioners' busyness favorably affect a company's initiative to publish climate change-related information. This study adds to the limited scholarly literature on the association between board characteristics and non-financial disclosure performance. It has significant implications for managers and regulators to pay closer attention to the effectiveness of commissioners' oversight in supporting company environmental actions.